Cell wall remodeling under abiotic stress - Tenhaken, Raimund (Frontiers in Plant Science, 2015)
Plants exposed to abiotic stress respond to the unfavorable conditions at multiple levels. One challenge under drought stress is to reduce shoot growth while maintaining root growth, a process requiring differential cell wall synthesis and remodeling. Key players in this process are the formation of reactive oxygen species (ROS) and peroxidases, which initially cross-link phenolic compounds and glycoproteins of the cell walls causing stiffening. The function of ROS shifts after having converted all of the peroxidase substrates in the cell wall. If ROS-levels remain high during prolonged stress, OH°-radicals are formed which lead to polymer cleavage. In concert with xyloglucan modifying enzymes and expansins, the resulting cell wall loosening allows further growth of stressed organs.